Artificial Intelligence in Healthcare in Indonesia: Are We Ready to Race for Golden Indonesia 2045? - I Wayan Sadwika (Jurnal Sosial Teknologi, 2026)
Indonesia stands at a decisive moment in implementing artificial intelligence (AI) to advance its healthcare system toward the Golden Indonesia 2045 vision. Despite promising clinical results, substantial gaps in infrastructure, regulation, and workforce capacity persist. This analytical review evaluates the current implementation of AI in Indonesian healthcare, identifies key barriers, and proposes strategic recommendations to achieve equitable and responsible AI integration aligned with national development goals. A narrative synthesis was conducted using targeted literature from PubMed, Google Scholar, Garuda, and SINTA (2020–2025), supplemented by national policy documents, SATUSEHAT governance reports, and Delphi consensus studies. Forty-two sources addressing clinical applications, regulatory frameworks, infrastructure, workforce readiness, and equity were thematically analyzed. Comparative benchmarking included regional maturity catalogues and international standards (EU AI Act, Singapore, Australia). AI demonstrates strong efficacy in diagnostics (e.g., 89.3% accuracy in diabetic retinopathy screening), telemedicine, and chronic disease management. However, Indonesia’s AI healthcare maturity score (52/100) lags behind Singapore (92) and Malaysia (78), constrained by fragmented regulation, rural digital divides, limited workforce AI literacy (≈58.7% lacking competence), and governance gaps in transparency and explainability. Coordinated policy reform, infrastructure investment, workforce training, and equity-focused implementation are essential to prevent technological dependency and fulfill AI’s potential for achieving universal health coverage by 2045.